Doping Effects and Grain Boundaries in Thermal CVD Graphene on Recrystallized Cu Foil. Issue 16 (6th June 2016) - Čermák, Jan; Yamada, Takatoshi; Ganzerová, Kristína; Rezek, Bohuslav
Abstract : Thermal chemical vapor deposition (CVD) of graphene on a copper (Cu) foil is strongly affected by Cu foil recrystallization and grain formation resulting in a heterogeneous graphene layer. Correlated microscopic scanning probe techniques show different chemical and structural properties (Raman microspectroscopy), electrical conductivity (conductive atomic force microscopy), and electronic structure (Kelvin probe force microscopy) across various types of grains. Graphene on clean Cu grains exhibits work function (WF) higher by 300 meV. This is attributed to the contact doping effect. Graphene of higher quality is formed on Cu grains with a surface cuprous oxide (Cu2 O) which forms during the thermal CVD process. The graphene WF is higher by 430 meV there. The WF difference is attributed to the contact doping effect and additional strain‐induced doping due to the highly corrugated Cu2 O surface. Local electrical conductivity measured by atomic force microscopy and a pair of conductive microprobes corroborates different graphene quality on various Cu grains and reveals that graphene is electrically interrupted at the Cu grain boundaries. Corresponding structural and electronic model of thermal CVD graphene on the Cu foil is presented. The correlation of grain boundaries in Cu foil and graphene is discussed. Abstract : Doping effects in graphene prepared by thermal chemical vapor deposition on a copper foil are detected by Kelvin probe force microscopy and supported by Raman microspectroscopy and microscopic conductivity measurements. The observed phenomena are attributed to the interaction between graphene and substrate, where cuprous oxide and Cu grain boundaries play the key role.